The process and logical mechanism of agricultural production space contraction in mountainous areas based on actor-network theory：A case study of Lishi Village in Longde County, Ningxia - CHEN Kunqiu, CHEN Yunya, LIANG Yajia, ZHENG Yuhan (Ziyuan Kexue)
[Objective] The rapid contraction of agricultural production space poses a threat to national food security, ecological safety and social stability. Clarifying the pattern and mechanism of agricultural production space contraction is of great significance to the high-quality development of agriculture and rural revitalization. [Methods] Based on the actor-network theory, this paper constructed a theoretical analysis framework for the agricultural production space contraction in mountainous areas. Taking Lishi Village in Longde County as an example, it used methods such as in-depth interviews and remote sensing interpretation to sort out the evolution process of the agricultural production space in the mountainous areas of southern Ningxia Hui Autonomous Region, and explore the underlying contraction mechanism. [Results] The study found that: (1) The translation of actor networks at different stages, the entry and exit of heterogeneous actors within the networks, and the transformation of the actor networks goals comprehensively contributed to the contraction of agricultural production space through the combined effects of human and non-human actors. (2) During the transformation of the actor network in Lishi Village, the key actor changed from the local government to the young labor force, and the obligatory point of passage (OPP) changed from “returning farmland to forest and grassland” to “developing specialty farming to maximize economic income”. (3) The agricultural production space in Lishi Village has gone through two stages: explicit contraction under the ecological objective and implicit contraction under the economic objective. (4) The contraction of agricultural production space in mountainous areas follows the mechanisms of environmental logic, policy-driven logic, and multi-subject logic. [Conclusion] To address the contraction of agricultural production space contraction in mountainous areas, it is necessary to innovate the mode of agricultural production and management, rationally balance the relationship between environmental carrying capacity and agricultural development, innovate the policies of ecological compensation and agricultural benefit, and accelerate the cultivation of new types of business entities such as elderly-friendly agriculture and professional farmers.